IBN KHALDUN’S POLITICAL THOUGHT AND RELEVANCE: ABDALLAH SHARIT’S CRITICAL PERSPECTIVE - Grine, Fadila; Khezzar, Ouassila Yaiche (Journal of Al-Tamaddun, 2018)
The critical review of contemporary Arab socio-politico-cultural in accordance with Abdallah Sharit show little change since Ibn Khaldun’s times, as there is no major difference from what is found in the Muqaddimah. Arab societies continue to live according to ‘asabiyyah, and struggle for political authority still continues to be the governing pattern despite making inroads towards nationalism. Abdallah Sharit explains the credibility and relevance of the Khaldunian concepts, while retaining the firm belief that the insight offered by Ibn Khaldun can potentially meet the needs of present-day Arab states. Within this context, Sharit finds that the ideas of Ibn Khaldun have become critically relevant to the existing socio-political configuration. This study explores both the manifestations and implications of Ibn Khaldun’s relevance to the present-day according to Sharit, especially regarding the pertinence of his political thought. It also assesses the relevance of Ibn Khaldun’s political thought in light of contemporary socio-political transformations taking place in the Arab world. This research also derives relevant lessons pertinent to our times, especially regarding what Sharit attempted to achieve through his study of Ibn Khaldun; while specifically seeking to emphasize Ibn Khaldun’s relevance to the interpretation and understanding of contemporary Arab conditions.